Preface - Kowalewski, T.A. (Archives of Mechanics, 2011)
This issue of the Archives of Mechanics contains six papers presented at the 19th Polish National Fluid Dynamics Conference (KKMP) hosted by Technical University of Poznań in September 5–9, 2010.